Analysis of risk factors causing short-term cement leakages and long-term complications after percutaneous kyphoplasty for osteoporotic vertebral compression fractures. (May 2018) - Gao, Chang; Zong, Min; Wang, Wen-tao; Xu, Lei; Cao, Da; Zou, Yue-fen
Background: Percutaneous kyphoplasty (PKP) is a common treatment modality for painful osteoporotic vertebral compression fractures (OVCFs). Pre- and postoperative identification of risk factors for cement leakage and follow-up complications would therefore be helpful but has not been systematically investigated. Purpose: To evaluate pre- and postoperative risk factors for the occurrence of short-term cement leakages and long-term complications after PKP for OVCFs. Material and Methods: A total of 283 vertebrae with PKP in 239 patients were investigated. Possible risk factors causing cement leakage and complications during follow-up periods were retrospectively assessed using multivariate analysis. Cement leakage in general, three fundamental leakage types, and complications during follow-up period were directly identified through postoperative computed tomography (CT). Results: Generally, the presence of cortical disruption ( P = 0.001), large volume of cement ( P = 0.012), and low bone mineral density (BMD) ( P = 0.002) were three strong predictors for cement leakage. While the presence of intravertebral cleft and Schmorl nodes ( P = 0.045 and 0.025, respectively) were respectively identified as additional risk factors for paravertebral and intradiscal subtype of cortical (C-type) leakages. In terms of follow-up complications, occurrence of cortical leakage was a strong risk factor both for new VCFs ( P = 0.043) and for recompression ( P = 0.004). Conclusion: The presence of cortical disruption, large volume of cement, and low BMD of treated level are general but strong predictors for cement leakage. The presence of intravertebral cleft and Schmorl nodes are additional risk factors for cortical leakage. During follow-up, the occurrence of C-type leakage is a strong risk factor, for both new VCFs and recompression.